Optimization of the Security and Safety Unit of the Karanganyar Traffic Police through Traffic Education for Society Programs to Reduce the Number of Traffic Accidents - Akhmad Fanani (Advances in Police Science Research Journal, 2024)
The research is motivated by the increasing number of traffic accidents in the jurisdiction of the Karanganyar Police Resort. The Karanganyar traffic police, in line with its main duties and functions, is responsible for reducing and preventing such problems. The security and safety unit is responsible for providing information on traffic safety and order to the public, particularly in the implementation of traffic education for society programs, to prevent traffic accidents. The research aims to describe the optimization of the security and safety Unit’s activities in traffic education and awareness programs to reduce the number of traffic accidents. The research used a qualitative approach, with field research method and data collection techniques using interviews and observations. The implementation of traffic education and for society programs was analyzed using management theories that can assess the stages of planning, organizing, implementing, and controlling. Meanwhile, the factors that influence the implementation were analyzed using covering both internal and external factors that affect traffic education for society programs. To optimize the implementation, management theory analysis tools such as planning, organizing, actuating, and controlling, and the 4M organizational resource theory were used such as Man, Money, Material, and Methode. Based on the research results, the implementation of traffic education for society programs and the optimization carried out by the security and safety Unit have not been optimal. In actual conditions, problems were found such as the absence of standard operating procedures as guidelines for implementation, limitations of security and safety unit members, limitations of facilities and infrastructure, and the failure to achieve the target of traffic education for society programs in the jurisdiction of the Karanganyar Police Resort. Therefore, there is a need for problem-solving or solutions to optimize the security and safety Unit’s activities in traffic education for society programs to reduce the number of traffic accidents.